Shifting critical listening class to virtual learning during the Covid-19 pandemic - Jhoni Eppendi (English Language Teaching Educational Journal, 2022)
Transforming the conventional face-to-face EFL learning into virtual learning has been believed to be an ideal alternative to education access in the middle of the COVID-19 outbreak. Hypothetically, abrupt transitions will require adaptation and rising practical predicament since the necessary toolkit must be allocated individually to conduct the listening Course. Thus, this study's purpose is to examine students' perception of the functioning of remote learning for Critical Listening class due to a prediction for drawing divergent language acquisition. This study involved forty-six students of the English education department at the Borneo University of Tarakan as research respondents. The data was recorded by distributing questionnaires and closed-ended questions through Google Forms and interview, while mixed analysis methodologies were applied. The questionnaire and interview result showed that students claim they struggle hard in the transitional phase and developing their educational outcomes. Most participants noticed an augmented listening performance in one teaching period, yet a higher chance of committing academic dishonesty than the prior learning circumstance. Therefore, the learning performance still needs enhancement in providing universally supported audios and solutions to plagiarism.